Insights on Conducting International Fieldwork in Developing Regions - Jill Zarestky (Adult Education Research Conference, 2015)
While issues of globalization deserve our attention, barriers to conducting international research may seem insurmountable. Having recently completed fieldwork in a developing region abroad, the purpose of this auto-ethnographic analysis was to examine the experience of conducting unfunded international field research as a means to support and encourage other scholars.
Keywords: international; auto-ethnography; methodology